Analysis of urban necessities reserve index and reserve quantity under emergency conditions - Jiang, Qijun; Ji, Xiaoyang; Rong, Zhijie (Frontiers in Public Health, 2024)
While maintaining a robust reserve of daily necessities is crucial for urban safety, but there is a lack of scientific basis for determining “what to store” and “how much to store.” This paper address this gap by classifying and summarizing the emergency materials of urban necessities in Shanghai, and establishing a corresponding reserve list. By constructing an index model of daily necessities reserve, this paper provides a scientific foundation for “what to store.” Additionally, the reserve levels of different types of daily necessities are classified and managed, the reserve model of emergency daily necessities is constructed. This approach clarifies the scientific basis for “how much to store,” overcoming the problems of subjective factors interference and the potential mismatch between the results of objective weighting method and reality. Furthermore, to better cope with emergencies, countermeasures and suggestions are put forward: optimizing the material structure of emergency reserves, managing the material reserves at different levels, scientifically and reasonably planning the amount of emergency materials, and reducing the cost of reserves and improve the efficiency of emergency reserves.